Impact of nitrogen addition on the chemical properties and bacterial community of subtropical forests in northern Guangxi - Jiang, Xingjian; Ou, Zhiyang; Tan, Changqiang; He, Qingfei; Zheng, Wei; Tan, Yibo; He, Feng; Shen, Hao (Frontiers in Microbiology, 2024)
In recent years, nitrogen deposition has constantly continued to rise globally. However, the impact of nitrogen deposition on the soil physicochemical properties and microbial community structure in northern Guangxi is still unclear.Along these lines, in this work, to investigate the impact of atmospheric nitrogen deposition on soil nutrient status and bacterial community in subtropical regions, four different nitrogen treatments (CK : 0 g N • m -2 • a -1 , II : 50 g N • m -2 • a -1 , III : 100 g N • m -2 • a -1 , IV : 150 g N • m -2 • a -1 ) were established. The focus was on analysing the soil physical and chemical properties, as well as bacterial community characteristics across varying nitrogen application levels. From the acquired results, it was demonstrated that nitrogen application led to a significant decrease in soil pH.Compared with CK, the pH of treatment IV decreased by 4.23%, which corresponded to an increase in soil organic carbon and total nitrogen. Moreover, compared with CK, the soil organic carbon of treatment IV increased by 9.28%, and the total nitrogen of treatment IV increased by 19.69%. However, no significant impact on the available nitrogen and phosphorus was detected. The bacterial diversity index first increased and then decreased with the increase of the nitrogen application level. The dominant phylum in the soil was Acidobacteria (34.63%-40.67%), Proteobacteria, and Chloroflexi. Interestingly, the abundance of Acidobacteria notably increased with higher nitrogen application levels, particularly evident in the IV treatment group where it surpassed the control group. Considering that nitrogen addition first changes soil nutrients and then lowers soil pH, the abundance of certain oligotrophic bacteria like Acidobacteria can be caused, which showed a first decreasing and then increasing trend. On the contrary, eutrophic bacteria, such as Actinobacteria and Proteobacteria, displayed a decline. From the redundancy analysis, it was highlighted that total nitrogen and pH were the primary driving forces affecting the bacterial community composition.